Registered nurses' exposure to workplace aggression in Norway: 12-month prevalence rates, perpetrators, and current turnover intention - Solveig Osborg Ose; Signe Lohmann-Lafrenz; Silje L. Kaspersen; Hanne Berthelsen; Gunn Hege Marchand (BMC, 2023)
Abstract Background Identifying occupational health hazards among Registered Nurses (RNs) and other health personnel and implementing effective preventive measures are crucial to the long-term sustainability of health services. The objectives of this study were (1) to assess the 12-month prevalence rates of exposure to workplace aggression, including physical violence, threats of violence, sexual harassment, and bullying; (2) to identify whether the perpetrators were colleagues, managers, subordinates, or patients and their relatives; (3) to determine whether previous exposure to these hazards was associated with RNs' current turnover intention; and (4) to frame workplace aggression from an occupational health and safety perspective. Methods The third version of the Copenhagen Psychosocial Questionnaire (COPSOQ III) was used to assess RNs' exposure to workplace aggression and turnover intention. A national sample of 8,800 RNs in Norway, representative of the entire population of registered nurses in terms of gender and geography, was analysed. Binary and ordinal logistic regression analyses were conducted, and odds for exposure and intention to leave are presented, with and without controls for RNs' gender, age, and the type of health service they work in. Results The 12-month prevalence rates for exposure were 17.0% for physical violence, 32.5% for threats of violence, 12.6% for sexual harassment, and 10.5% for bullying. In total, 42.6% of the RNs had experienced at least one of these types of exposure during the past 12 months, and exposure to more than one of these hazards was common. Most perpetrators who committed physical acts and sexual harassment were patients, while bullying was usually committed by colleagues. There was a strong statistical association between exposure to all types of workplace aggression and RNs' intention to leave. The strongest association was for bullying, which greatly increased the odds of looking for work elsewhere. Conclusions Efforts to prevent exposure to workplace aggression should be emphasised to retain health personnel and to secure the supply of skilled healthcare workers. The results indicate a need for improvements. To ensure the sustainability of health services, labour and health authorities should join forces to develop effective workplace measures to strengthen prevention, mitigation, and preparedness regarding incidents of workplace aggression in health services and the response and recovery regarding incidents that could not be prevented.